The Effectiveness of Liquidity, Solvency, and Profitability Ratios against the Stock Returns of the Company - Hedwigis Esti Riwayati; Markonah Markonah; Maratus Sholeha (MIX: JURNAL ILMIAH MANAJEMEN, 2023)
Objectives: A company’s bottom line analysis is one of the essential factors that should be done by the shareholders when deciding to invest their shares in the company. It gives a clear view of whether shares will be bought, sold, or retained. This research aims to reveal the effectiveness of liquidity which is represented by current ratio (CR) solvency in the form of debt-to-equity ratio (DER) and profitability proxies by return on equity (ROE) towards Stock returns in service sector Industries.Methodology: The research population used consists of 76 service sector firms that are active in the property, real estate, and building construction sectors that are registered at the Indonesia Stock Exchange. The purposive method is used as the sampling technique with a total sample of 22 service companies. The data used in this study were gathered from financial reports during 2016-2020. Panel data regression is performed while the analysis technique is processed through E-views 9.Finding The results indicate the implementation of the fixed effect model has found that liquidity in this case is the current ratio and profitability which is represented by ROE showed that variables do not affect stock returns while solvency which is represented by debt-to-equity ratio has an impact on the stock returns. The current ratio does not affect the return on equity, while the debt-to-equity ratio has a negative effect on return on equity. The current ratio and debt-to-equity ratio mediated by return on equity do not affect stock returns.Conclusion: High liquidity indicates an increase in company performance but in this case, liquidity is still not considered as a determining factor for investors in investing because investors are more focused on the use of capital and debt.